Sympathetic ophthalmia: Enucleation or evisceration? - Manandhar, A (Nepalese Journal of Ophthalmology, 2011)
The purpose of this review is to find out the risk of sympathetic ophthalmia after evisceration and enucleation particularly in a case of penetrating ocular (non-surgical or surgical) injury and to know about the cosmetic outcome of evisceration and enucleation. Ophthalmologists around the world, whenever dealing with a case of penetrating ocular (non-surgical or surgical) injury, might thus be helped in deciding whether to keep the traumatized eye or remove it. And if they finally decide to remove it, they will be able to choose between evisceration and enucleation for the best cosmetic outcome, and to minimize the risk of sympathetic ophthalmia. The results of the review are the following. Enucleation is not found to be the best protective measure against development of sympathetic ophthalmia, as it was thought to be, since there are ample reports of sympathetic ophthalmia occurring not just after evisceration but also after enucleation. The cosmetic outcome of evisceration as opposed to enucleation is found to be better. Key words: sympathetic ophthalmia, enucleation, evisceration DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5274 Nepal J Ophthalmol 2011; 3(2): 181-187